Prospects and Challenges for The African Continental Free Trade Area (AFCFTA) in Africa’s Economic Growth - Obari Alale Osaro (Research Parks Publishers, 2025)
The paper discusses the prospects and challenges of the African Continental Free Trade Agreement (AfCFTA) as an agent of development in Africa. It is a well-known fact that Africa occupies the lower rungs of the ladder in the global index of development. As a result, many of the people of Africa live in serious conditions of poverty. To deal with the problem the African Union (AU) established AfCFTA as one of the agents that can be used to promote development on the continent. The author used a number of primary sources like the papers of the Economic Commission for Africa (ECA), AU papers, and secondary sources like books and articles to carry out the research. The Endogenous theory which posits that economic growth and development are best promoted by the use of internal resources is used as the major theoretical framework. Overall, the study revealed that AfCFTA can provide the enabling framework to foster a strong intra-African trade and eventually engender growth and development on the continent. However, the paper identifies the non-development character of the state in postcolonial Africa weak infrastructural base, and the activities of the erstwhile colonial masters as factors that can hamper the success of AfCFTA.